Leadership style analysis of the Head of Sukahurip Village, Pangandaran District - Azzahra, Dananir Hasna; Rizkiani, Nadia Aulia; Katiah, K. (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
To build village development, parties who can synergise for the programs that will be held in a village, such as the village head, village officials, and the village community are needed. Sukahurip Village is a village located in Pangandaran Regency, which is currently carrying out sustainable development. In the process, the development was assisted by the village head, who was the leader in its management. The village head often involves the community in decision-making. The role of the leader here is important in fulfilling all of these services, starting from the planning and implementation processes. The leader must apply the right leadership style to encourage or move the community to achieve the vision and mission of the village as an advanced village. Therefore, descriptive research is needed regarding the leadership style applied by the Sukahurip Village Head, the results of which can be used for the next Village Head to optimize the potential of his village to carry out sustainable development. This study uses qualitative methods with data collection techniques using interviews and observations. The research data collection method was carried out through interviews, holding a meeting of two people to exchange information and ideas through question and answer so that meaning can be constructed in a particular topic, and observation, which is data collection by observing the subject or phenomenon under study without direct intervention.